THE ROLE OF TEACHING ISLAMIC RELIGION AT SEKOLAH ALAM INDONESIA PALEMBANG - Aida Imtihana; Sukirman Sukirman; Mardeli Mardeli; Nurlela Nurlela (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
The weakness of the schools in the emergence of Islamic education curriculum is the lack of facilities provided for the benefits of its curriculum. Islamic education curriculum in schools is systematic, so it cannot resolve the issue of the overall gap because it is limited to the other aspects like a limited time allocation. Therefore, Sekolah Alam Indonesia Palembang was established to optimize the learning of Islamic education. The results of this study showed that the learning process of Islamic education at the school has been in accordance with the theory of planning, implementation, and evaluation. The planning instruction consists of an annual, semester, weekly and daily program planning. In practice, the learning process is based on the planning that has been made. Further, to evaluate the learning process, oral and written tests were conducted.